Exposure to mass disaster and probable panic disorder among children in New York City. (June 2021) - Goodwin, Renee D.; Cheslack-Postava, Keely; Musa, George J.; Eisenberg, Ruth; Bresnahan, Michaeline; Wicks, Judith; Weinberger, Andrea H.; Fan, Bin; Hoven, Christina W.
Abstract: While both direct and indirect exposure to mass trauma are increasing in the United States, relatively little is known about the potential link between mass trauma and risk of panic disorder early in life. It is also unclear whether history of prior individual trauma increases risk of panic disorder even further among those with exposure to mass trauma. The current study investigated the association between exposure to a mass trauma event (the World Trade Center (WTC) attack) and risk of panic disorder among children, how panic disorder varies by exposure severity and sociodemographic characteristics, and whether there is an interaction between individual and mass trauma exposure in the risk of panic disorder. Data were from an epidemiologic study of probable mental disorders among New York City schoolchildren exposed to the WTC terrorist attack. Severe (adjusted odds ratio [AOR] = 2.0 (1.1, 3.7)) exposure to the WTC disaster was associated with increased odds of probable panic disorder, relative to mild exposure. The prevalence of panic disorder increased with higher level of WTC exposure among all sociodemographic strata. Prior individual trauma exposure was associated with increased odds of panic disorder (AOR = 2.4 (1.6, 3.5)), but there was no evidence of interaction between prior individual trauma exposure and exposure to the WTC disaster. Preventive measures to address the widespread nature of mass disaster exposure at increasingly earlier ages and via media could mitigate the potential impact on mental health. Highlights: Severe exposure to 9/11 was associated with probable panic disorder. Prior individual trauma was also associated with probable panic disorder. No statistical interaction was found between individual trauma and exposure to 9/11. Attendance at a Ground Zero school was not associated with probable panic disorder.